Odpowiedź:
[tex]1)\ \ 2\frac{1}{3}+\not3\cdot\frac{2}{\not3}=2\frac{1}{3}+2=4\frac{1}{3}\\\\2)\ \ (4,4-2)\cdot\frac{5}{8}=2,4\cdot\frac{5}{8}=\frac{\not24^3}{\not10_{2}}\cdot\frac{\not5^1}{\not8_{1}}=\frac{3}{2}=1\frac{1}{2}\\\\3)\ \ \frac{4}{5}+2,4:0,4-0,2=0,8+6-0,2=0,6+6=6,6\\\\4)\ \ 10\frac{2}{3}-2\frac{1}{3}+\frac{2}{3}=8\frac{1}{3}+\frac{2}{3}=8\frac{3}{3}=9[/tex]
[tex]5)\ \ 3,6\cdot\frac{5}{12}-\frac{1}{2}\cdot3=\frac{\not36^3}{\not10_{2}}\cdot\frac{\not5^1}{\not12_{1}}-\frac{3}{2}=\frac{3}{2}-\frac{3}{2}=0\\\\6)\ \ (12-3,6:2)\cdot4=(12-1,8)\cdot4=10,2\cdot4=40,8\\\\\\1\ \ \ \ \ \ 2\ \ \ \ \ \ 3\ \ \ \ \ \ 4\ \ \ \ \ \ 5\ \ \ \ \ \ 6\\\\B\ \ \ \ A\ \ \ \ \ \ N\ \ \ \ A\ \ \ \ \ \ \ C\ \ \ \ H\\\\\\Stefan\ \ Banach[/tex]